Crises and Disruptions in International Business How Multinational Enterprises Respond to Crises - Mithani, Murad A.; Narula, Rajneesh; Surdu, Irina; Verbeke, Alain (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
Crises and disruptions can lead to important changes in economic, social and institutional environments. This collection of influential JIBS articles and original commentaries highlights that MNEs are affected by, and respond to, crises and disruptions differently than domestic firms due to their geographically dispersed operations and wider range of experiences from being active in diverse environments. MNEs can exhibit greater flexibility to 'avoid' locations characterised by crises and disruptions, and when affected, they can deploy a more refined set of responses relative to domestic firms. Each article is accompanied by a new editorial piece, bringing the research right up to date and reflecting on the impact of the article today. The book offers an integrated perspective on the antecedents, outcomes and potential opportunities associated with a variety of crises and disruptions such as disease outbreaks, natural disasters, climate change and political unrest. An ideal resource for students and researchers, this book offers new perspectives, policy and practical recommendations as well as a discussion of future trends. .
Part 1: Introduction -- 1. Unique Implications of Crises and Disruptions for International Business: How MNEs Are Exposed to Crises and Mitigate Their Effects -- Part-2: Multi-Stakeholder Pressures and Political Conflict -- 2. Speculation in International Crises: Report from the Gulf -- 3. Global Closure, Crises and Financial Markets: A Commentary -- 4. Why and How Might Firms Respond Strategically to Violent Conflict? -- 5. New 'Dominant Logic' on How Firms Respond to Crises: A Commentary -- 6. Why and How Might the Modern MNE Respond Strategically to Violent Conflict: A Commentary -- Part-3 Conflict Zones, Firm Strategy and MNE Performance Outcomes -- 7. Place, Space, and Geographical Exposure: Foreign Subsidiary Survival in Conflict Zones -- 8. Place and Space in Foreign Subsidiary Exit from Conflict Zones: A Commentary -- 9. Impact of Historical Conflict on FDI Location and Performance: Japanese Investment in China -- 10. Foreign Direct Investment and Military Conflicts: A Commentary -- Part-4 Climate Change, Climate Risk and MNE Strategy -- 11. A Perspective on Multinational Enterprises and Climate Change: Learning from "an Inconvenient Truth"? -- 12. International Business, Climate Change and the Energy Transition: A Commentary on the Importance of Business Models and Digitalization -- 13. The Impact of Climate Risk on Firm Performance and Financing Choices: An International Comparison -- 14. The Impact of Climate Risk on Firm Performance and Financing Choices: A Commentary -- Part-5 The Impact of Crises and Disruptions on Local Market Strategies and Legitimacy -- 15. Liability of Foreignness, Natural Disasters, and Corporate Philanthropy -- 16. Liability of Foreignness, Natural Disasters, and Corporate Philanthropy: A Commentary -- 17. International HRM Insights for Navigating the COVID-19 Pandemic: Implications for Future Research and Practice -- 18. The Impact of COVID-19 on International HRM Research and Practice: A Commentary -- Part-6 Conclusion -- 19. Moving Forward in a Post-Covid World.
Keywords: International business enterprises; International Business